(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to study the importance of applying lean accounting techniques and the tools and methods they contain, the most important of which is the “value path costs” technique and its impact on rationalizing and controlling costs, as well as reducing production costs in general and reducing quality costs in a way Special by reducing or eliminating waste and waste in both time and resources and meeting customer requirements. In order to achieve this goal, the researcher relied on the application of lean accounting tools by obtaining data related to the mill, in addition to that, the information obtained as a result of field coexistence in the mill and being able to view the records of the mill in the research sample. From the foregoing, the researcher reached several conclusions, the most important of which is that Al-Taji Mill adopts the traditional concepts of cost accounting and is far from the concepts of rationalization and the tools it includes, through which it is possible to rationalize and reduce production costs in general and reduce quality costs in particular, in addition to not listening sufficiently to the customer’s voice for the purpose of Achieving his satisfaction, which is one of the most important main ingredients for achieving the goals and success of the economic unit, which is the customer who directs the unit towards production and marketing.